Improving patient complaint mechanisms in Malaysia: the role of law and medical organisations - Jahn Kassim, Puteri Nemie (IIUMPress, 2009)
One of the most important ironies of modern health care is that public expectations are rising faster than the ability of health services to meet them. Patients nowadays no longer want to be treated as passive recipients of medical care. Instead, they want to be treated but as co-producers or partners able to manage their illnesses. Thus, it is not surprising that poor communication and failure to take into account the patient's perspective are at the heart of most formal complaints and legal actions in Malaysia. The difficulties of existing complaint procedures in Malaysia have become manifested over the years and this has been accentuated by patients becoming more willing to challenge the decisions of medical practitioners and health service management in court. To reduce the number of complaints and risks of litigation, a more patient-centred approach should be adopted. When patients voiced their concern by making a complaint or inquiry, this should be seen as a unique source of information for health care services on why adverse events occur and how to prevent them. As well as reducing future harm to patients, better management of complaints should restore trust and reduce the risk of litigation, through open communication and a commitment to learn from the problem. Various models on patient complaint mechanisms, particularly, in Australia and England can provide valuable insight for future reforms. Presently, the existing procedures for patients to be heard in Malaysia should be reviewed and incorporate features such as responsiveness, accessibility, impartiality, simplicity, speed and accountability.